READING COMPREHENSION -- REREADING - Ochilova, Vazirakhon (Eurasian Journal of Academic Research, 2022)
Strong foundations in reading, writing, and speaking language are requirements for students. Sadly, some pupils are lagging behind in their literacy development. Being able to read and understand what is read is a necessary skill for being a full citizen in today’s information-driven environment. Learning to read well at a young age is essential for children’s growth and intellectual development as well as for them to succeed in school.